Phenotypic and genotypic characterization of nonO1/ nonO139 Vibrio cholerae from aquaculture farm sediments - Reethy, P. S.; Lalitha, K. V. (Fishery Technology, 2020)
Toxigenic Vibrio cholerae is a major public healthproblem in developing countries andlysogenicconversion of naturally occurring nontoxigenic V.cholerae strains by a lysogenic filamentous bacteriophageCTXÃ– has also been demonstrated. Theaim of this study was to analyse phenotypic andgenotypic characteristics of V. cholerae strains fromsediments in aquaculture settings. Based on biochemical,molecular and serological assays confirmedthe presence of fourty nine nonO1/nonO139V.cholerae strains from fifty six sediment samples.PCR assays revealed that all V.cholerae strainsharboured toxR, hlyA and ompW genes. But none ofthe virulent genessuch as ctxA, tcpA, ace and zot werepresent in all tested strains. Antibiotic susceptibilityto different antibacterial agents was also performedby disc diffusion assay. This result has shown 26.5%of the non-O1/non-O139 V.cholerae isolates weremultidrug resistant for three classes of antibiotics.Genetic diversity of nontoxigenic V.cholerae isolatedfrom aquaculture farm sedimentswas determined byERIC PCR.The genetic diversity studies revealedclonal relationship among the various non-O1/non-O139 isolates.